2010
DOI: 10.1093/glycob/cwq049
|View full text |Cite
|
Sign up to set email alerts
|

Developmental stage-dependent expression of an  2,8-trisialic acid unit on glycoproteins in mouse brain

Abstract: The monoclonal antibody mAb.A2B5 is a marker for the detection of oligodendrocyte progenitor cells that differentiate into type-2 astrocytes and oligodendrocytes. It is also a useful antibody for separating these cells from other lineage populations. The epitope of this antibody is considered to be the gangliosides GT3 and GQ1c. In this study, we sought to define more precisely the structure of the epitope. Accordingly, we chemically synthesized defined oligosialic acid structures linked to phosphatidylethanol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 61 publications
1
28
0
Order By: Relevance
“…C, real-time PCR for mRNA expression of WGA16. The expression level in each organ was normalized by the expression of actin mRNA as described (27). The relative expression is shown relative to that of testis set to 1.0.…”
Section: Discussionmentioning
confidence: 99%
“…C, real-time PCR for mRNA expression of WGA16. The expression level in each organ was normalized by the expression of actin mRNA as described (27). The relative expression is shown relative to that of testis set to 1.0.…”
Section: Discussionmentioning
confidence: 99%
“…Turnover of Cell-surface PolySia Is Rapid and Mediated by an Induced Extracellular Sialidase-PolySia is known to turnover a period of days during postnatal brain development (7,34), and this is presumed to be due to internalization and lysosomal degradation. However, the possibility that polySia might turn over rapidly on the cell surface has not been previously considered.…”
Section: Turnover Of Polysia On Microglial Cells Under Inflammatorymentioning
confidence: 99%
“…In fact, lysosome-associated membrane protein-1 has been identified as a major SSEA-1 carrier protein in mouse neural stem cells [112]. Furthermore, it has been recently reported that the epitope of A2B5 antigens, c-series gangliosides used as marker carbohydrates of glial precursor cells and brain cancer stem cells, was also carried by 4 glycoproteins in developing mouse brains [113]. There is a possibility that the immunoreactivity of stem cells to antibodies to SSEA-3, SSEA-4, and GD2 are also attributable to glycoproteins or proteoglycans but not to glycolipids.…”
Section: Future Subjectmentioning
confidence: 99%